Understanding social innovation as an innovation process: Applying the innovation journey model - Oeij, Peter R. A.; van der Torre, Wouter; Vaas, Fietje; Dhondt, Steven (Journal of Business Research, 2019)
The innovation journey is a process model distinguishing between the initiation, developmental and implementation/termination period of innovations; it looks at drivers and barriers, like innovation managers, investors, setbacks, adaptation, infrastructure. We operationalize this model to apply it to the process of social innovation. Eighty-two cases are re-analysed in a secondary analysis using qualitative comparative analysis to assess how social innovations develop and to investigate if they resemble the ‘innovation journey’ of innovations in technology/business.
Keywords: Innovation sociale; Processus d'innovation